Rhapsodomantik, mannakorn og tommelfingervers - Petersen, Anders Klostergaard (Religionsvidenskabeligt Tidsskrift, 2003)
<p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; line-height: normal; tab-stops: .95pt 14.2pt 28.4pt 35.4pt 42.65pt 56.85pt 70.8pt 85.3pt 99.5pt 106.2pt 113.75pt 127.95pt 141.6pt 156.4pt 170.6pt 177.0pt 184.85pt 199.05pt 212.4pt 227.5pt 241.0pt 247.8pt 255.95pt 269.35pt 10.0cm 298.6pt 312.8pt 318.6pt 327.05pt 354.0pt 389.4pt 424.8pt 460.2pt;">Divination and mantics play a decisive role in ancient as well as modern religiosity. Although the subjects are not an integral part of the current curriculums for theology and the study of religion, they are pivotal for understanding religion and religious practices, especially of the ancient world. In this paper, which is the first part of a larger research project on divination and mantics of early Christianity and ancient Judaism, I explore one particular form of mantics: rhapsodomantics, i.e. divination by means of Sacred Books that are either randomly opened or used in order to provide ‘slips’ upon which verses from the Books in question are written. The randomly chosen textual passage is secondarily interpreted and explained in terms of a divinely inspired guidance. In this manner the lot oracle provides access to the understanding of the divine world. The ritual consultance of lot oracles is simultaneously a way of domesticising the contingency and arbitrariness of life. By means of a ritually staged display of arbitrariness (the random drawing of lots), arbitrariness is mastered. <p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; line-height: normal; tab-stops: .95pt 14.2pt 28.4pt 35.4pt 42.65pt 56.85pt 70.8pt 85.3pt 99.5pt 106.2pt 113.75pt 127.95pt 141.6pt 156.4pt 170.6pt 177.0pt 184.85pt 199.05pt 212.4pt 227.5pt 241.0pt 247.8pt 255.95pt 269.35pt 10.0cm 298.6pt 312.8pt 318.6pt 327.05pt 354.0pt 389.4pt 424.8pt 460.2pt;">First – based on recent insights from the field of cognitive science (primarily Whitehouse and Boyer), semiotics, the tradition of sociology of knowledge and ritual studies – I discuss imagistic thought in contrast to doctrinaire modes of religiosity. Second, I scrutinize the ritual raison d’être for divination and mantics. <p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; line-height: normal; tab-stops: .95pt 14.2pt 28.4pt 35.4pt 42.65pt 56.85pt 70.8pt 85.3pt 99.5pt 106.2pt 113.75pt 127.95pt 141.6pt 156.4pt 170.6pt 177.0pt 184.85pt 199.05pt 212.4pt 227.5pt 241.0pt 247.8pt 255.95pt 269.35pt 10.0cm 298.6pt 312.8pt 318.6pt 327.05pt 354.0pt 389.4pt 424.8pt 460.2pt;">The second part of the paper presents an analysis of numerous texts exemplifying rhapsodomantics. In a recent book by the Swedish novelist P.O. Enquist Lewis Rejse, narrating the founding of the Pentecostal Church of Sweden, the ritual practice of using ‘Thumble verses’ and ‘Manna seeds’ plays a decisive role in the founding of the community. As a point of departure relevant excerpts from this book are discussed in order to travel back to the Märchenland of the ancient world. Numerous Greco-Roman, Jewish and Early Christian examples of rhapsodomantics are discussed and related to recent analyses by van der Horst and Potter.